Analisis Portfolio Concentration dan Insurance Leverage terhadap Kemampulabaan Perusahaan Asuransi yang Tercatat di Bei Tahun 2009-2021 dengan Mediasi Struktur Modal - Gandung Troy Sulistyantoro; Dewi Hanggraeni (Syntax Literate, 2023)
Among the various types of risks, the probability that most often occurs is operational risk, including insurance companies in Indonesia. This study aims to analyze and examine the effect of operational risk based on portfolio concentration and insurance leverage on the profitability of insurance companies with capital structure moderation factors. Data was obtained from the Indonesia Stock Exchange between 2009-2021, using the Structural Equation Model and Path Analysis method approaches. The first result of the study is that capital structure has a negative influence on the profitability of insurance companies, but not significantly. Second, the positive relationship between operational risk to capital structure, or capital structure is also positively influenced by operational risk significantly. Third, the capital structure mediates negatively the effect of operational risk on the profitability of insurance companies.